A morte: centralidade e significado em Hans Jonas - Tasca, Mariana Goron (2021)
This thesis addresses the changes that the meaning of death has undergone throughout the development of civilization. As the theme unfolds, Philosopher Hans Jonas arrives in his Philosophical Biology, in which the Ontology of Life is rethought, and in this metaphysical journey, he arrives at his proposal for Integral Monism. Literates and philosophers who addressed the subject covered serve as substrate for the understanding of death, as well as its escape, to which the most diverse tricks are employed, as always, by men. Implied in this context, an investigation of the advancement of techno-sciences, in addition to including bioethics and biomedicine, is fundamental in the sense of thinking about their limits that impact not only the future of humanity but life in general. The present thesis elevates death to an common thread to the philosopher's work, and also will analyze whether, and under what conditions, death, after all, is welcome in nature